Uterine perforation by Bakri balloon following management of secondary postpartum haemorrhage: a case report and review of literature - Bahuguna, Gunjan; Kalaskar, Anjali; Viswanatha, Radhika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The objective of this study was to decipher the efficacy and safety of the Bakri balloon as a tamponading device for managing secondary postpartum haemorrhage. A 37-year-old lady presented to us with a secondary postpartum haemorrhage after 17 days of vaginal birth. Due to ongoing heavy bleeding per vaginum, she underwent an examination under anaesthesia, and manual removal of placental tissue along with the insertion of a Bakri balloon under ultrasound guidance. However, after 6 hours of the procedure, she deteriorated and the bedside ultrasound showed rupture of the uterus at the fundus with the Bakri balloon in situ. She was resuscitated and had an emergency laparotomy with repair of the uterine perforation following which she recovered completely and was discharged home on day 6. Uterine rupture following balloon tamponade is a rare but life-threatening complication, especially when placed during the management of secondary PPH in a septic postpartum uterus. This occurred despite placing the balloon under ultrasound guidance in an unscarred uterus. Keeping a low threshold of suspicion of uterine rupture and prompt treatment can save the uterus. The safety of the use of the Bakri balloon in secondary PPH needs to be reviewed in a larger population as the uterus is more likely to rupture because of underlying infection.